Mapping of zones for modeling of perennial forages in mixed-crop livestock systems in Kenya - Nyawira, Sylvia Sarah; Korir, Mercy Jebet; Maina, Wilson Nguru; Notenbaert, An Maria Omer (2023)
The data contains spatial data of precipitation, temperature, elevation, topographical wetness index (TWI), slope and soil texture used in the mapping of zones for modeling perennial forages in mixed-crop livestock systems in Kenya. The R-code used in the zonal mapping as well as the method used a description of the approach is also included. The identified zones will be applied for modeling with DSSAT CROPGRO perennial forage model.